The grammatical responses of Ibn Hisham in the footnote - Hariz, Taghreed; Laibi, Zahraa (Al-Adab Journal, 2023)
The grammatical responses of Ibn Hisham varied in the footnote, some of which were in the structure of the millennium, and some of them were grammatical responses, and his response was to a grammatical doctrine, or to a specific scholar, and he mentioned what he saw as correct, and justified that, citing what his memory helped from the blessed Quranic verses or the hadiths of the Prophet, or poetic verses, and sometimes the grammarians make mistakes without explaining the cause. And he responded to the grammarians on some issues, and he was deluded in his response to some of the grammarians in attributing a wrong opinion to them, and then he responds to this opinion, as Ibn Jinni and Ibn al-Nazim; The copy that was in the hands of Ibn Hisham contained an alteration or distortion. The reason for this is due to the lack of printing at that time, so this copy may have been mistakenly transmitted by its author.